Earlier mathematics achievement and success in university studies - Murtonen, Mari; Titterton, Nathaniel (NOMAD Nordic Studies in Mathematics Education, 2004)
This study explores connections between earlier mathematics achievement in high school, success in university statistics and quantitative methods courses and experienced difficulties in quantitative methods courses. Earlier achievement in mathematics correlated with statistics grade in university studies, but not with quantitative methods course grade. Earlier achievement in mathematics was related to the experience of one’s own ability in mathematical subjects and quantitative methods, but it was not related to other experienced difficulties. Ability in mathematical subjects and quantitative methods was further connected to other difficulties experienced in quantitative methods. The experienced difficulties and achievement in university courses were not related.